An improved stable downward continuation of potential fields using a truncated Taylor series and regularized vertical derivatives method. (19th June 2018) - Gang, Yin; Lin, Zhang
Abstract: Downward continuation of potential field plays an important role in the interpretation of gravity and magnetic field data. For its inherent instability, the continuation operation is extremely sensitive to noise. In this paper, we present an improved stable downward continuation method based on the computation of stable vertical derivatives obtained by the Tikhonov regularization and the truncated Taylor series expansion of the field. By using the Tikhonov regularization operator in the frequency domain, the filtering is also performed simultaneously while computing the vertical derivatives, and then the stable derivatives and downward continuation are obtained. The calculation results of synthetic and real data show that the proposed method can achieve stable and accurate downward continuation for the magnetic data.